Wilfred Trotter: surgeon, philosopher - Rosen, Irving B. (Canadian Medical Association, 2006)
There is no significant biography that records the accomplishments of Sir Wilfred Trotter, who was a general surgeon in its pure sense at a time when surgical specialization was in its infancy. Trotter was born in the 1870s in England. Despite being bedridden during his childhood with a musculoskeletal condition he was able to study medicine at London University, and eventually became Professor and Chair of Surgery at the University College Hospital, a position he held until his death in November 1939. He made many contributions to surgical care, particularly in the field of oncology. He attended to many famous people, including King George V and Sigmund Freud and was greatly honoured in his own milieu. He was named honorary surgeon and Sargent Surgeon to the king. In addition, he was a thoughtful individual who addressed problems in human behaviour, contradicting the stereotype of the contemporary surgeon.